Titanium dioxide coated carbon quantum dot hybrid silicon dioxide microsphere and cream glue

By using silane-functionalized carbon quantum dot hybrid silica microspheres in cream glue and coated with anatase-type titanium dioxide, the problems of antibacterial and fluorescent anti-counterfeiting functions of cream glue are solved, and performance improvement and simplicity of the method are achieved.

CN119242293APending Publication Date: 2025-01-03ZHEJIANG WADOU CREATIVE ART CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411204602.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing cream glues are prone to mold and long bacteria during use and have counterfeit and inferior products, lack effective antibacterial and fluorescent anti-counterfeiting functions, and titanium dioxide and carbon quantum dots are prone to agglomeration when added to cream glue, resulting in poor performance.

Method used

Using silane-functionalized carbon quantum dot hybrid silica as the core layer, the surface is coated with anatase titanium dioxide through hydrothermal reaction to form a core-shell structure of titanium dioxide coated carbon quantum dot hybrid silica microspheres. Avoid direct contact between the two, ensure even distribution and add to the cream glue.

Benefits of technology

It realizes the excellent antibacterial and fluorescent anti-counterfeiting functions of cream glue, avoids fluorescence quenching, and is simple and suitable for promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242293A_ABST
    Figure CN119242293A_ABST
Patent Text Reader

Abstract

The invention relates to the field of white glue, and discloses titanium dioxide coated carbon quantum dot hybrid silicon dioxide microspheres and cream glue. The titanium dioxide coated carbon quantum dot hybrid silicon dioxide microsphere is of a core-shell structure, a core layer is carbon quantum dot hybrid silicon dioxide, and a shell layer is anatase type titanium dioxide; the carbon quantum dots are silane functionalized carbon quantum dots and are doped in silicon dioxide in situ. Silane functionalized carbon quantum dot hybrid silicon dioxide is used as a core layer, the surface of the core layer is coated with titanium dioxide, and large-area direct contact between the carbon quantum dots and titanium dioxide can be avoided while uniform distribution of the carbon quantum dots is ensured, so that the fluorescence quenching phenomenon can be avoided; the obtained titanium dioxide coated carbon quantum dot hybrid silicon dioxide microspheres have excellent antibacterial and fluorescent anti-counterfeiting functions. The titanium dioxide coated carbon quantum dot hybridized silicon dioxide microspheres are simply added into cream glue as a filler, so that the cream glue can be endowed with excellent antibacterial and fluorescent anti-counterfeiting functions, and the preparation method is simple and suitable for popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of white glue, in particular to titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microspheres and cream glue. Background Art

[0002] With the rise of the DIY handcraft craze and the continuous improvement of safety awareness, a new type of water-based environmentally friendly special white glue, cream glue, has emerged. Cream glue is not only rich in color and texture, but also has a large creative space. It is particularly suitable for decoration and production of exquisite and collectible DIY handcrafts. However, with the increase of usage time and changes in the surrounding environment, cream glue is prone to mold and bacteria. At the same time, the low cost of imitation of cream glue has led to a large number of counterfeit and shoddy products on the market, which seriously damages the reputation of enterprises and the rights and interests of consumers. Therefore, it is necessary to develop a cream glue with good antibacterial and fluorescent anti-counterfeiting properties.

[0003] Titanium dioxide has the advantages of excellent chemical stability, environmental protection and excellent photocatalytic performance. Especially under ultraviolet light, titanium dioxide produces strong oxidizing substances such as hydroxyl radicals and hydrogen peroxide, which can effectively destroy the cell walls of bacteria and other biomacromolecules and have antibacterial effects. On the other hand, carbon quantum dots, as an environmentally friendly fluorescent nanomaterial, have the advantages of low cost, high fluorescence yield and good biocompatibility. They have gradually become a hot spot in the field of luminescent material research and have important application value in the field of anti-counterfeiting.

[0004] In summary, if titanium dioxide and carbon quantum dots are used as raw materials in cream glue, theoretically, the cream glue can have antibacterial and fluorescent anti-counterfeiting functions. However, at present, there is no precedent for applying titanium dioxide and carbon quantum dots to cream glue at the same time. To this end, the applicant has made attempts in the early stage, and found that if titanium dioxide and carbon quantum dots are simply added to the cream glue, titanium dioxide and carbon quantum dots are prone to agglomeration, resulting in the inability to give full play to their antibacterial properties and fluorescent anti-counterfeiting properties, especially carbon quantum dots will experience fluorescence quenching. Therefore, how to apply titanium dioxide and carbon quantum dots to cream glue while ensuring that titanium dioxide and carbon quantum dots do not interfere with each other, so that the cream glue has excellent antibacterial function and fluorescent anti-counterfeiting performance, is a problem that needs to be solved at present. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a titanium dioxide-coated carbon quantum dot hybrid silica microsphere and cream glue. The present invention uses silane-functionalized carbon quantum dot hybrid silica as the core layer, and coats titanium dioxide on its surface. While ensuring the uniform distribution of carbon quantum dots, it can avoid large-area direct contact between them and titanium dioxide, thereby avoiding the phenomenon of fluorescence quenching. The obtained titanium dioxide-coated carbon quantum dot hybrid silica microsphere has excellent antibacterial fluorescence anti-counterfeiting function. The titanium dioxide-coated carbon quantum dot hybrid silica microsphere of the present invention is simply added to the cream glue as a filler to give the cream glue excellent antibacterial fluorescence anti-counterfeiting function. The preparation method is simple and suitable for promotion.

[0006] The specific technical scheme of the present invention is: In the first aspect, the present invention provides a titanium dioxide-coated carbon quantum dot hybridized silica microsphere, which has a core-shell structure, wherein the core layer is carbon quantum dot hybridized silica, and the shell layer is anatase titanium dioxide. The carbon quantum dots are silane-functionalized carbon quantum dots, which are in-situ doped in silica.

[0007] The titanium dioxide-coated carbon quantum dot hybridized silica microspheres of the present invention have carbon quantum dot hybridized silica as the core and anatase titanium dioxide as the shell, and therefore have antibacterial fluorescent anti-counterfeiting functions. Moreover, in the present invention, the carbon quantum dots are uniformly hybridized in the silica shell, which can avoid a large amount of direct contact between the carbon quantum dots and titanium dioxide, prevent the two from interfering with each other, and thus avoid the phenomenon of fluorescence quenching. Adding it to cream glue can give the cream glue excellent antibacterial function and fluorescent anti-counterfeiting performance.

[0008] In addition, the present invention finds that if titanium dioxide is used as the core layer and carbon quantum dot hybridized silica is used as the shell layer, the antibacterial property of titanium dioxide in the final product will be affected. The reasons are analyzed as follows: on the one hand, the antibacterial property of titanium dioxide will be affected by the pore size of the silica shell layer; on the other hand, in the process of titanium dioxide being converted into anatase crystal form by hydrothermal reaction, the surface is shielded by the silica shell layer, which will affect its crystal form and thus affect its antibacterial property.

[0009] Preferably, the silane-functionalized carbon quantum dots are obtained by hydrothermal reaction using an organic acid as a carbon source and an amino-containing silane as a passivating agent.

[0010] Preferably, the carbon quantum dot hybrid silica is obtained by dehydration condensation of a silicon source in an alkaline environment, and at the same time, silane-functionalized carbon quantum dots are introduced into the reaction system, and silicic acid produced by hydrolysis of the silicon source undergoes dehydration condensation with silane of the silane-functionalized carbon quantum dots.

[0011] Preferably, the anatase titanium dioxide is firstly hydrolyzed by a titanium source under alkaline conditions to form a titanium dioxide shell on the surface of the carbon quantum dot hybridized silicon dioxide, and then converted into anatase through a hydrothermal reaction.

[0012] In a second aspect, the present invention provides a method for preparing the above-mentioned titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microspheres, comprising the following steps: 1) Silane-functionalized carbon quantum dots were synthesized by a hydrothermal method using organic acid as a carbon source and amino-containing silane as a passivating agent.

[0013] 2) Dehydration and polycondensation of the silicon source in an alkaline environment, while introducing silane-functionalized carbon quantum dots into the reaction system, the silicic acid produced by hydrolysis of the silicon source and the silane of the silane-functionalized carbon quantum dots undergo dehydration and condensation to obtain carbon quantum dot hybrid silica.

[0014] 3) The titanium source is hydrolyzed under alkaline conditions to form a shell layer on the surface of the carbon quantum dot hybridized silica.

[0015] 4) subjecting the product obtained in 3) to a hydrothermal reaction to obtain titanium dioxide-coated carbon quantum dot hybrid silica microspheres having carbon quantum dot hybrid silica as a core layer and anatase titanium dioxide as a shell layer.

[0016] The preparation principle of the titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microspheres of the present invention is as follows Figure 1 As shown. Specifically: In step 1), the organic acid forms a carbon core after dehydration, polymerization and carbonization, and the amino functional group of the passivator undergoes an amidation reaction with the carboxyl group on the surface of the carbon core, so that the crystal nucleus grows into a silane-functionalized carbon quantum dot. In step 2), the silane-functionalized carbon quantum dots are introduced into a silicon source, and the silicon source is hydrolyzed in an alkaline environment to produce silicic acid, and the silicic acid undergoes dehydration condensation with the silane on the surface of the silane-functionalized carbon quantum dots to form Si-O-Si bonds, thereby hybridizing the carbon quantum dots in the three-dimensional skeleton structure of the long chain of silica to form carbon quantum dot hybrid silica microspheres. In step 3), the titanium source is hydrolyzed under alkaline conditions, and the hydrolysis product undergoes dehydration condensation with the silanol group on the surface of the carbon quantum dot hybrid silica microspheres to form Si-O-Ti bonds, thereby coating the surface of the carbon quantum dot hybrid silica microspheres. In step 4), titanium dioxide is converted into anatase through a hydrothermal reaction, thereby having excellent antibacterial properties, and finally titanium dioxide-coated carbon quantum dot hybrid silica microspheres with antibacterial fluorescent anti-counterfeiting functions are obtained.

[0017] Preferably, step 1) specifically comprises: mixing an organic acid, an amino-containing silane and water, and performing a hydrothermal reaction to obtain silane-functionalized carbon quantum dots.

[0018] Preferably, in step 1), the usage ratio of the organic acid, the amino-containing silane and water is 0.25 g:(3-7) mL:(3-7) mL.

[0019] Preferably, in step 1), the temperature of the hydrothermal reaction is 160-200° C., and the reaction time is 10-15 h.

[0020] Preferably, step 2) specifically comprises: mixing and heating water, alkali solution and ethanol, adding silicon source, ethanol and silane functionalized carbon quantum dots under stirring, reacting, separating, and obtaining carbon quantum dot hybridized silica.

[0021] Preferably, in step 2), the ratio of water, alkali solution and first added ethanol is 3 mL: (6-10) mL: (30-35) mL; the heating temperature is 50-70° C., and the stirring rate is 300-500 rpm.

[0022] Preferably, in step 2), the amount ratio of the silicon source, the ethanol added for the second time and the silane-functionalized carbon quantum dots is 4 mL: (10-20) mL: (280-320) μL; and the reaction time is 1-3 h.

[0023] Preferably, step 3) specifically comprises: mixing ethanol, acetonitrile and the product of 2) and then dispersing them by ultrasonication, adding alkali solution and titanium source after stirring, reacting, and separating the product.

[0024] Preferably, in step 3), the dosage ratio of ethanol, acetonitrile, the product obtained in step 2), alkali solution and titanium source is 100 mL: (40-50) mL: (0.05-0.15) g: (0.4-0.8) mL: (0.4-0.8) mL; the ultrasonic dispersion time is 0.5-1.5 h; the stirring rate is 400-600 rpm; and the reaction time is 4-5 h.

[0025] The present invention finds that in step 3), by optimizing the ratio of the carbon quantum dot hybrid silica and the titanium source obtained in step 2), it can ensure that the final titanium dioxide-coated carbon quantum dot hybrid silica microspheres have both excellent antibacterial properties and fluorescence. If the amount of titanium source is too small, the product will have insufficient antibacterial properties; conversely, if the amount of titanium source is too large, it is easy to cause the titanium dioxide shell formed to be too thick, which will shield the fluorescence of the carbon quantum dots to a certain extent. Finally, the present invention finds that the effect is better under the above ratio.

[0026] Preferably, step 4) specifically comprises: mixing the product of 3) with ethanol and water, dispersing them ultrasonically, performing a hydrothermal reaction, and separating the product to obtain titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microspheres; Preferably, in step 4), the dosage ratio of ethanol, water and the product of 3) is 80 mL: (30-50) mL: (0.05-0.15) g; the ultrasonic dispersion time is 0.5-1.5 h; the hydrothermal reaction temperature is 150-170° C., and the reaction time is 15-25 h.

[0027] In a third aspect, the present invention provides an antibacterial fluorescent anti-counterfeiting cream glue, comprising the following raw materials in parts by weight: 0.001-0.1 parts of titanium dioxide-coated carbon quantum dot hybrid silica microspheres, 5-15 parts of polymer emulsion, 10-20 parts of calcium carbonate, 1-3 parts of solvent, 0-0.1 parts of wetting agent, 0-0.15 parts of defoaming agent, and 0-0.1 parts of sodium carboxymethyl cellulose.

[0028] Preferably, the polymer emulsion includes one or more of pure acrylic emulsion, hydroxypropyl emulsion and EVA emulsion.

[0029] Preferably, the wetting agent includes one or more of alkyl polyoxyethylene ether, polyether silicone and non-ionic fluorocarbon polymers; alkyl polyoxyethylene ether is further preferred.

[0030] Preferably, the defoaming agent includes one or more of silicones, mineral oils, polyethers and higher alcohols; and FB-50 silicone defoaming agent is further preferred.

[0031] In a fourth aspect, the present invention provides a method for preparing an antibacterial fluorescent anti-counterfeiting cream glue, comprising: S1: adding calcium carbonate, a wetting agent, a solvent, titanium dioxide-coated carbon quantum dot hybrid silica microspheres and a defoaming agent to a polymer emulsion under stirring.

[0032] S2: Add sodium carboxymethyl cellulose and continue stirring to obtain the finished product.

[0033] Since the titanium dioxide-coated carbon quantum dot hybrid silica microspheres of the present invention have excellent antibacterial fluorescent anti-counterfeiting functions, they can be given corresponding functions by simply adding them to the raw materials of cream glue as fillers. The preparation method is simple and suitable for promotion.

[0034] Preferably, in S1, the stirring speed is 300-400 rpm, and the stirring time is 20-40 min.

[0035] Preferably, in S2, the stirring speed is 300-400 rpm, and the stirring time is 20-40 min.

[0036] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention uses silane-functionalized carbon quantum dot hybrid silica as the core layer and coats titanium dioxide on its surface. While ensuring uniform distribution of carbon quantum dots, it can avoid large-area direct contact between them and titanium dioxide, thereby avoiding fluorescence quenching. The obtained titanium dioxide-coated carbon quantum dot hybrid silica microspheres have excellent antibacterial fluorescent anti-counterfeiting functions.

[0037] (2) Simply adding the titanium dioxide-coated carbon quantum dot hybrid silica microspheres of the present invention as fillers into the cream glue can give the cream glue excellent antibacterial fluorescent anti-counterfeiting function. The preparation method is simple and suitable for promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a schematic diagram of the preparation principle of titanium dioxide-coated carbon quantum dot hybrid silica microspheres in Example 1.

[0039] Figure 2 These are the XRD spectra of carbon quantum dot hybrid silica (SiO2 / CQD) and titanium dioxide-coated carbon quantum dot hybrid silica (SiO2 / CQD@TiO2) in Example 1.

[0040] Figure 3 SEM images of titanium dioxide-coated carbon quantum dots hybrid silica (SiO2 / CQD@TiO2) at different magnifications for implementation 1.

[0041] Figure 4 These are digital photos of the carbon quantum dot solution in Example 1 under natural light and ultraviolet light.

[0042] Figure 5 These are digital photos of titanium dioxide-coated carbon quantum dot hybrid silica (SiO2 / CQD@TiO2) microspheres and carbon quantum dot hybrid silica microspheres (SiO2 / CQD) in Example 1 under natural light and ultraviolet light.

[0043] Figure 6 These are digital photos of the cream glue of Examples 1, 2 and Comparative Example 1 under natural light and ultraviolet light. DETAILED DESCRIPTION

[0044] The present invention will be further described below in conjunction with the embodiments.

[0045] Overall embodiment In a first aspect, a titanium dioxide-coated carbon quantum dot hybridized silicon dioxide microsphere is provided, which has a core-shell structure, wherein the core layer is carbon quantum dot hybridized silicon dioxide, and the shell layer is anatase titanium dioxide. The carbon quantum dots are silane-functionalized carbon quantum dots, which are in-situ doped in silicon dioxide.

[0046] In some preferred implementation cases, the silane-functionalized carbon quantum dots are obtained by hydrothermal reaction using organic acid as a carbon source and amino-containing silane as a passivating agent.

[0047] In some preferred implementation cases, the carbon quantum dot hybrid silica is obtained by dehydration condensation of a silicon source in an alkaline environment, and at the same time, silane-functionalized carbon quantum dots are introduced into the reaction system, and the silicic acid produced by hydrolysis of the silicon source undergoes dehydration condensation with the silane of the silane-functionalized carbon quantum dots.

[0048] In some preferred implementation cases, the anatase titanium dioxide is first hydrolyzed by a titanium source under alkaline conditions to form a titanium dioxide shell on the surface of the carbon quantum dot hybridized silica, and then converted into anatase through a hydrothermal reaction.

[0049] The above-mentioned titanium dioxide coated carbon quantum dot hybridized silica microspheres of the present invention are with carbon quantum dot hybridized silica as the core and anatase titanium dioxide as the shell, so they have antibacterial fluorescence anti-counterfeiting function. Moreover, in the present invention, carbon quantum dots are uniformly hybridized in the silica shell, which can avoid a large amount of direct contact between carbon quantum dots and titanium dioxide, prevent the two from interfering with each other, and thus avoid causing fluorescence quenching. Adding it to the cream glue can give the cream glue excellent antibacterial function and fluorescent anti-counterfeiting performance. In addition, the present invention finds that if titanium dioxide is used as the core layer and carbon quantum dot hybridized silica is used as the shell layer, the antibacterial property of titanium dioxide in the final product will be affected, and the reason for this is that: on the one hand, the antibacterial property of titanium dioxide will be affected by the pore size of the silica shell layer, and on the other hand, in the process of titanium dioxide being converted into anatase crystal form by hydrothermal reaction, the surface is shielded by the silica shell layer, which will affect its crystal form, thereby affecting its antibacterial property.

[0050] In a second aspect, a method for preparing the titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microspheres comprises the following steps: 1) Silane-functionalized carbon quantum dots were synthesized by a hydrothermal method using organic acid as a carbon source and amino-containing silane as a passivating agent.

[0051] In the above step 1), the organic acid forms a carbon core after dehydration, polymerization and carbonization, and the amino functional group of the passivating agent undergoes an amidation reaction with the carboxyl group on the surface of the carbon core, so that the crystal core grows into a silane-functionalized carbon quantum dot.

[0052] In some preferred implementation cases, step 1) specifically includes: mixing an organic acid, an amino-containing silane and water, and obtaining silane-functionalized carbon quantum dots through a hydrothermal reaction.

[0053] In some more preferred implementation cases, the ratio of the organic acid, the amino-containing silane and water is 0.25 g: (3-7) mL: (3-7) mL. In some preferred implementation cases, the temperature of the hydrothermal reaction is 160-200° C., and the reaction time is 10-15 h.

[0054] 2) Dehydration and polycondensation of the silicon source in an alkaline environment, while introducing silane-functionalized carbon quantum dots into the reaction system, the silicic acid produced by hydrolysis of the silicon source and the silane of the silane-functionalized carbon quantum dots undergo dehydration and condensation to obtain carbon quantum dot hybrid silica.

[0055] In the above step 2), silane-functionalized carbon quantum dots are introduced into a silicon source, and the silicon source is hydrolyzed in an alkaline environment to produce silicic acid, and silicic acid undergoes dehydration condensation with silane on the surface of the silane-functionalized carbon quantum dots to form Si-O-Si bonds, thereby hybridizing the carbon quantum dots in the three-dimensional skeleton structure of the long chain of silica to form carbon quantum dot hybridized silica microspheres.

[0056] In some preferred implementation cases, step 2) specifically includes: mixing and heating water, alkali solution and ethanol, adding silicon source, ethanol and silane functionalized carbon quantum dots under stirring, reacting, separating, and obtaining carbon quantum dot hybrid silica.

[0057] In some more preferred implementation cases, the ratio of water, alkali solution and first added ethanol is 3 mL: (6-10) mL: (30-35) mL; the heating temperature is 50-70° C., and the stirring rate is 300-500 rpm.

[0058] In some more preferred implementation cases, the usage ratio of the silicon source, the second added ethanol and the silane-functionalized carbon quantum dots is 4 mL: (10-20) mL: (280-320) μ; and the reaction time is 1-3 h.

[0059] 3) The titanium source is hydrolyzed under alkaline conditions to form a shell layer on the surface of the carbon quantum dot hybridized silica.

[0060] In the above step 3), the titanium source is hydrolyzed under alkaline conditions, and the hydrolysis product undergoes dehydration condensation with the silanol groups on the surface of the carbon quantum dot hybrid silica microspheres to generate Si-O-Ti bonds, thereby coating the surface of the carbon quantum dot hybrid silica microspheres.

[0061] In some preferred implementation cases, step 3) specifically comprises: mixing ethanol, acetonitrile and the product of 2) and then dispersing them by ultrasonication, adding alkali solution and titanium source after stirring, reacting, and separating the product.

[0062] In some more preferred implementation cases, the dosage ratio of ethanol, acetonitrile and the product obtained in 2), alkali solution and titanium source is 100mL: (40-50)mL: (0.05-0.15)g: (0.4-0.8)mL: (0.4-0.8)mL; the ultrasonic dispersion time is 0.5-1.5h; the stirring rate is 400-600rpm; and the reaction time is 4-5h.

[0063] 4) The product obtained in step 3) is subjected to a hydrothermal reaction to obtain titanium dioxide-coated carbon quantum dot hybrid silica microspheres having carbon quantum dot hybrid silica as a core layer and anatase titanium dioxide as a shell layer.

[0064] In the above step 4), titanium dioxide is converted into anatase through a hydrothermal reaction, thereby having excellent antibacterial properties, and finally titanium dioxide-coated carbon quantum dot hybrid silica microspheres with antibacterial fluorescent anti-counterfeiting functions are obtained.

[0065] In some preferred implementation cases, step 4) specifically comprises: mixing the product of 3) with ethanol and water, dispersing by ultrasonication, performing a hydrothermal reaction, and separating the product to obtain titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microspheres; In some more preferred implementation cases, the dosage ratio of ethanol, water and 3) product is 80mL: (30-50)mL: (0.05-0.15)g; the ultrasonic dispersion time is 0.5-1.5h; the hydrothermal reaction temperature is 150-170°C, and the reaction time is 15-25h.

[0066] The present invention finds that in step 3), by optimizing the ratio of the carbon quantum dot hybrid silica and the titanium source obtained in step 2), it can ensure that the final titanium dioxide-coated carbon quantum dot hybrid silica microspheres have both excellent antibacterial properties and fluorescence. If the amount of titanium source is too small, the product will have insufficient antibacterial properties; conversely, if the amount of titanium source is too large, it is easy to cause the titanium dioxide shell formed to be too thick, which will shield the fluorescence of the carbon quantum dots to a certain extent. Finally, the present invention finds that the effect is better under the above ratio.

[0067] In a third aspect, an antibacterial fluorescent anti-counterfeiting cream glue comprises the following raw materials in parts by weight: 0.001-0.1 parts of titanium dioxide-coated carbon quantum dot hybrid silica microspheres, 5-15 parts of polymer emulsion, 10-20 parts of calcium carbonate, 1-3 parts of solvent, 0-0.1 parts of wetting agent, 0-0.15 parts of defoaming agent, and 0-0.1 parts of sodium carboxymethyl cellulose.

[0068] Since the titanium dioxide-coated carbon quantum dot hybrid silica microspheres of the present invention have excellent antibacterial fluorescent anti-counterfeiting functions, they can be given corresponding functions by simply adding them to the raw materials of cream glue as fillers. The preparation method is simple and suitable for promotion.

[0069] In some preferred implementation cases, the polymer emulsion includes one or more of pure acrylic emulsion, hydroxypropyl emulsion and EVA emulsion.

[0070] In some preferred implementation cases, the wetting agent includes one or more of alkyl polyoxyethylene ether, polyether silicone and non-ionic fluorocarbon polymers; alkyl polyoxyethylene ether is further preferred.

[0071] In some preferred implementation cases, the defoaming agent includes one or more of silicones, mineral oils, polyethers and high-carbon alcohols; FB-50 silicone defoaming agent is further preferred.

[0072] In a fourth aspect, a method for preparing an antibacterial fluorescent anti-counterfeiting cream glue comprises: S1: Add calcium carbonate, a wetting agent, a solvent, titanium dioxide-coated carbon quantum dot hybrid silica microspheres and a defoaming agent into the polymer emulsion under stirring.

[0073] S2: Add sodium carboxymethyl cellulose and continue stirring to obtain the finished product.

[0074] In some preferred implementation cases, in S1, the stirring speed is 300-400 rpm, and the stirring time is 20-40 min.

[0075] In some preferred implementation cases, in S2, the stirring speed is 300-400 rpm, and the stirring time is 20-40 min.

[0076] Specific Examples and Comparative Examples Example 1 The first step is to prepare titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microsphere powder with antibacterial and fluorescent anti-counterfeiting functions, including the following steps: (1) Add 0.25 g of citric acid, 5 ml of AEAPMS, and 5 ml of deionized water into the inner container of a reactor; the hydrothermal reaction temperature is 180° C. and the reaction time is 12 h to obtain silane-functionalized carbon quantum dots; (2) Place a three-necked flask in a water bath, add 32 ml of ethanol, 3 ml of deionized water and 8 ml of ammonia (26 wt%) in sequence, heat to 60 °C at a stirring speed of 400 rpm, then add 4 ml of TEOS, 0.4 ml of silane-functionalized carbon quantum dots and 15 ml of ethanol in sequence, and react for 2 h; (3) dropping the reaction product into a centrifuge tube, centrifuging at 6000 rpm, separating the precipitate, washing it three times with ethanol and deionized water respectively, and then drying it in an oven at 60° C. for 12 h to obtain a dry carbon quantum dot hybrid silica microsphere powder; (4) Take 0.1g of carbon quantum dot hybrid silica microsphere powder in a beaker, pour in 100ml of acetonitrile and 45ml of ethanol and ultrasonically disperse for 1h. Then pour into a three-necked flask, add 0.6ml of ammonia water (26wt%), stir at 500rpm for 30min, then add 0.6ml of TBOT and react for 4.5h; (5) The reaction product was dropped into a centrifuge tube and centrifuged at 6000 rpm to separate the precipitate. The precipitate was washed three times with ethanol and deionized water respectively, and then dried in a 60°C oven for 12 hours. The powder was then poured into a beaker, 80 ml of ethanol and 40 ml of deionized water were added, and ultrasonic dispersion was performed for 1 hour. Finally, the powder was poured into a reactor and hydrothermally reacted at 160°C for 20 hours. (6) The reaction product was dropped into a centrifuge tube and centrifuged at 6000 rpm to separate the precipitate, which was washed three times with ethanol and deionized water respectively, and then dried in an oven at 60° C. for 12 h to obtain a dry titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microsphere powder.

[0077] The second step is to prepare the cream glue with antibacterial and fluorescent anti-counterfeiting effects, which includes the following steps: (1) Add 10 g of EVA emulsion (solid content 55 wt%) into a beaker; (2) Stirring at a speed of 350 rpm, 10 g of calcium carbonate, 0.5 g of alkyl polyoxyethylene ether wetting agent, 2 g of water, 0.1 g of titanium dioxide-coated carbon quantum dot hybrid silica microspheres and 0.1 g of FB-50 type silicone defoaming agent were sequentially added for 30 minutes, and then 0.2 g of sodium carboxymethyl cellulose thickener was added and the stirring and mixing was continued for 30 minutes to obtain a cream glue with antibacterial and fluorescent anti-counterfeiting properties.

[0078] Example 2 The first step is to prepare titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microsphere powder with antibacterial and fluorescent anti-counterfeiting functions, including the following steps: (1) Add 0.25 g of citric acid, 5 ml of AEAPMS, and 5 ml of deionized water into the inner container of a reactor; the hydrothermal reaction temperature is 180° C. and the reaction time is 12 h to obtain silane-functionalized carbon quantum dots; (2) Place a three-necked flask in a water bath, add 32 ml of ethanol, 3 ml of deionized water and 8 ml of ammonia (26 wt%) in sequence, heat to 60 °C at a stirring speed of 400 rpm, then add 4 ml of TEOS, 0.4 ml of silane-functionalized carbon quantum dots and 15 ml of ethanol in sequence, and react for 2 h; (3) dropping the reaction product into a centrifuge tube, centrifuging at 6000 rpm, separating the precipitate, washing it three times with ethanol and deionized water respectively, and then drying it in an oven at 60° C. for 12 h to obtain a dry carbon quantum dot hybrid silica microsphere powder; (4) Take 0.1g of carbon quantum dot hybrid silica microsphere powder in a beaker, pour in 100ml of acetonitrile and 45ml of ethanol and ultrasonically disperse for 1h. Then pour into a three-necked flask, add 0.6ml of ammonia water (26wt%), stir at 500rpm for 30min, then add 0.6ml of TBOT and react for 4.5h; (5) The reaction product was dropped into a centrifuge tube and centrifuged at 6000 rpm to separate the precipitate. The precipitate was washed three times with ethanol and deionized water respectively, and then dried in a 60°C oven for 12 hours. The powder was then poured into a beaker, 80 ml of ethanol and 40 ml of deionized water were added, and ultrasonic dispersion was performed for 1 hour. Finally, the powder was poured into a reactor and hydrothermally reacted at 160°C for 20 hours. (6) The reaction product was dropped into a centrifuge tube and centrifuged at 6000 rpm to separate the precipitate, which was washed three times with ethanol and deionized water respectively, and then dried in an oven at 60° C. for 12 h to obtain a dry titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microsphere powder.

[0079] The second step is to prepare the cream glue with antibacterial and fluorescent anti-counterfeiting effects, which includes the following steps: (1) Add 10 g of EVA emulsion (solid content 55 wt%) into a beaker; (2) Stirring at a speed of 350 rpm, 10 g of calcium carbonate, 0.5 g of alkyl polyoxyethylene ether wetting agent, 2 g of water, 0.05 g of titanium dioxide-coated carbon quantum dot hybrid silica microsphere powder and 0.1 g of FB-50 type silicone defoamer were sequentially added for 30 minutes, and then 0.2 g of sodium carboxymethyl cellulose thickener was added and the stirring and mixing was continued for 30 minutes to obtain a cream glue with antibacterial and fluorescent anti-counterfeiting properties.

[0080] Comparative Example 1 The preparation of the cream glue comprises the following steps: (1) Add 10 g of EVA emulsion (solid content 55 wt%) into a beaker; (2) 10 g of calcium carbonate, 0.5 g of alkyl polyoxyethylene ether wetting agent, 2 g of water and 0.1 g of FB-50 type silicone defoaming agent were sequentially added with stirring at a speed of 350 rpm for 30 minutes, and then 0.2 g of sodium carboxymethyl cellulose thickener was added and the stirring and mixing was continued for 30 minutes to obtain a cream gel.

[0081] Performance Testing and Characterization Figure 2 The XRD spectra of carbon quantum dot hybrid silica (SiO2 / CQD) and titanium dioxide coated carbon quantum dot hybrid silica (SiO2 / CQD@Tio2) in Example 1 are shown in FIG. Figure 2As shown, the broad peak of carbon quantum dot hybrid silica between 16° and 30° corresponds to the amorphous diffraction peak of amorphous silica, and the characteristic peaks of titanium dioxide-coated carbon quantum dot hybrid silica at 2θ angle positions of 25.26°, 37.78°, 47.86°, 53.98°, 55.22°, 62.56°, 69.93°, 70.17° and 75.13° correspond to the (101), (004), (200), (105), (211), (204), (116), (220) and (215) crystal planes of anatase titanium dioxide crystal form (PDF#71-1166). The results show that the reaction product is composed of silicon dioxide and titanium dioxide.

[0082] Figure 3 The SEM images of titanium dioxide coated carbon quantum dot hybrid silicon dioxide (SiO2 / CQD@TiO2) at different magnifications in Example 1 are shown in FIG. Figure 3 As shown, the shape of titanium dioxide-coated carbon quantum dots hybrid silicon dioxide is spherical, and the average particle size is 370 nm.

[0083] Figure 4 The digital photos of the carbon quantum dot solution in Example 1 under natural light and ultraviolet light. Figure 4 As shown, under natural light, the carbon quantum dot solution is transparent, and under ultraviolet light with a wavelength of 365nm, the carbon quantum dot solution produces strong fluorescence.

[0084] Figure 5 The digital photos of the carbon quantum dot hybrid silica microsphere powder (SiO2 / CQD) and the titanium dioxide coated carbon quantum dot hybrid silica microsphere powder (SiO2 / CQD@TiO2) in Example 1 under natural light and ultraviolet light. Figure 5 As shown, under ultraviolet light of 365nm wavelength, both powders produce fluorescence effect, among which the fluorescence effect of carbon quantum dot hybrid silica microsphere powder is stronger than that of titanium dioxide coated carbon quantum dot hybrid silica microsphere powder.

[0085] Figure 6 The digital photos of the cream glue of Examples 1, 2 and Comparative Example 1 under natural light and ultraviolet light are shown in FIG. Figure 6 As shown, under natural light, it appears white. Under ultraviolet light, Examples 1 and 2 produce strong fluorescence, while Comparative Example 1 produces no fluorescence, and by comparing Examples 1 and 2, it can be seen that as the amount of titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microsphere powder increases, the fluorescence effect produced becomes stronger.

[0086] Table 1 shows the antibacterial rate of cream glue containing titanium dioxide coated carbon quantum dots hybrid silica by plate counting method. The test sample and the control sample were mixed with the bacterial solution respectively, and after constant temperature culture at 37°C for 24 hours, the antibacterial rate was calculated by coating plate counting, and the results are shown in Table 1. It can be seen from the table that the antibacterial fluorescent anti-counterfeiting cream glue has good antibacterial ability against Escherichia coli and Staphylococcus aureus. As the content of titanium dioxide coated carbon quantum dots hybrid silica microsphere powder increases, the antibacterial ability of the antibacterial fluorescent anti-counterfeiting cream glue increases.

[0087] Table 1 Type of bacteria Escherichia coli Staphylococcus aureus Example 1 88.5% 89.4% Example 2 82.1% 83.2% Comparative Example 1 10.1% 9.5% The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0088] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microsphere, characterized in that: It has a core-shell structure, with the core layer being carbon quantum dot hybridized silica and the shell layer being anatase titanium dioxide; The carbon quantum dots are silane functionalized carbon quantum dots, which are in-situ doped in silicon dioxide.

2. The titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microspheres according to claim 1, characterized in that: The silane-functionalized carbon quantum dots are obtained by hydrothermal reaction using organic acid as a carbon source and amino-containing silane as a passivating agent; The carbon quantum dot hybrid silica is obtained by dehydration condensation of a silicon source in an alkaline environment, and at the same time, silane-functionalized carbon quantum dots are introduced into the reaction system, and silicic acid produced by hydrolysis of the silicon source and silane of the silane-functionalized carbon quantum dots undergo dehydration condensation; The anatase titanium dioxide is firstly hydrolyzed by a titanium source under alkaline conditions to form a titanium dioxide shell on the surface of the carbon quantum dot hybridized silicon dioxide, and then converted into anatase through a hydrothermal reaction.

3. A method for preparing titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microspheres according to claim 1, characterized in that include: 1) Using organic acid as carbon source and amino-containing silane as passivating agent, silane-functionalized carbon quantum dots were synthesized by hydrothermal method; 2) Dehydration and polycondensation of the silicon source in an alkaline environment, while introducing silane-functionalized carbon quantum dots into the reaction system, and dehydration and condensation of silicic acid produced by hydrolysis of the silicon source and silane of the silane-functionalized carbon quantum dots to obtain carbon quantum dot hybrid silica; 3) The titanium source is hydrolyzed under alkaline conditions to form a shell layer on the surface of carbon quantum dot hybrid silica; 4) The product obtained in 3) is subjected to a hydrothermal reaction to obtain titanium dioxide-coated carbon quantum dot hybrid silica microspheres having carbon quantum dot hybrid silica as a core layer and anatase titanium dioxide as a shell layer.

4. The preparation method according to claim 3, characterized in that: Step 1) specifically comprises: mixing an organic acid, an amino-containing silane and water, and performing a hydrothermal reaction to obtain silane-functionalized carbon quantum dots; The organic acid, amino-containing silane and water are used in a ratio of 0.25 g: (3-7) mL: (3-7) mL; The temperature of the hydrothermal reaction is 160-200° C., and the reaction time is 10-15 hours.

5. The preparation method according to claim 3, characterized in that: Step 2) specifically includes: Mix water, alkali solution and ethanol and heat them, add silicon source, ethanol and silane functionalized carbon quantum dots under stirring, react and separate to obtain carbon quantum dot hybrid silica; The water, alkali solution and first added ethanol are used in a ratio of 3 mL: (6-10) mL: (30-35) mL; the heating temperature is 50-70° C., and the stirring rate is 300-500 rpm; The usage ratio of the silicon source, the ethanol added for the second time and the silane-functionalized carbon quantum dots is 4 mL: (10-20) mL: (280-320) μL; and the reaction time is 1-3 h.

6. The preparation method according to claim 3, characterized in that: Step 3) specifically includes: Mix ethanol, acetonitrile and the product of 2) and disperse them by ultrasonication, add alkali solution and titanium source after stirring, react, and separate the product; The dosage ratio of the ethanol, acetonitrile, the product obtained in 2), the alkali solution and the titanium source is 100 mL: (40-50) mL: (0.05-0.15) g: (0.4-0.8) mL: (0.4-0.8) mL; the ultrasonic dispersion time is 0.5-1.5 h; the stirring rate is 400-600 rpm; and the reaction time is 4-5 h.

7. The preparation method according to claim 3, characterized in that: Step 4) specifically includes: The product of 3) is mixed with ethanol and water, and then dispersed by ultrasonication, subjected to hydrothermal reaction, and the product is separated to obtain titanium dioxide-coated carbon quantum dot hybrid silicon dioxide microspheres; The dosage ratio of ethanol, water and 3) product is 80 mL: (30-50) mL: (0.05-0.15) g; the ultrasonic dispersion time is 0.5-1.5 h; the hydrothermal reaction temperature is 150-170° C., and the reaction time is 15-25 h. 8.An antibacterial fluorescent anti-counterfeiting cream glue, characterized in that The invention comprises the following raw materials in parts by weight: 0.001-0.1 parts of the titanium dioxide-coated carbon quantum dot hybrid silica microspheres according to claim 1 or 2 or the titanium dioxide-coated carbon quantum dot hybrid silica microspheres obtained by the preparation method according to any one of claims 3 to 7, 5-15 parts of polymer emulsion, Calcium carbonate 10-20 parts, 1-3 parts of solvent, Wetting agent 0-0.1 parts, Defoaming agent 0-0.15 parts, Sodium carboxymethyl cellulose 0-0.1 parts.

9. The antibacterial fluorescent anti-counterfeiting cream glue according to claim 8, characterized in that: The polymer emulsion includes one or more of pure acrylic emulsion, hydroxypropyl emulsion and EVA emulsion; The wetting agent includes one or more of alkyl polyoxyethylene ether, polyether silicone and non-ionic fluorocarbon polymer; The defoaming agent includes one or more of silicones, mineral oils, polyethers and higher alcohols.

10. A method for preparing the antibacterial fluorescent anti-counterfeiting cream glue according to claim 8 or 9, characterized in that include: S1: adding calcium carbonate, a wetting agent, a solvent, titanium dioxide-coated carbon quantum dot hybrid silica microspheres and a defoaming agent to the polymer emulsion under stirring; S2: Add sodium carboxymethyl cellulose and continue stirring to obtain the finished product.